O papel da matriz sobre os padrões de diversidade da comunidade de aves em fragmentos de Mata Atlântica - Fagner Daniel Teixeira (2015)
Forest is restricted to small isolated patches in all its extension and, as a consequence, the majority of its fauna is declining or under extinction risk. This is observed due mainly to habitat loss and other negative effects that take place on patches in a landscape, including the edge effect, which influences both biotic and abiotic factors. Nevertheless, it is important to be careful while generalizing since different matrices can influence patches in distinct levels. For example, planted forest phytophysionomies can act as barriers to the border effect when compared to open areas, such as pastures. Therefore, we hypothesize that patches in contact with a matrix dominated by eucalyptus would have more diverse bird communities. We assessed the richness, abundance and functional diversity of birds in the edge and inside patches of Atlantic Forest surrounded by pastures (n=4) and by eucalyptus trees (n=4). Even though all the studied patches showed low species richness and approximate values, the eucalyptus matrix seems to favor the bird community, as we found higher species richness and evenness in the border of the fragments surrounded by eucalyptus. Furthermore the community in contact with the eucalyptus matrix had a greater functional diversity, abundance of groups generally sensitive to disturbances and presence of a threatened species. It is important to give more attention to the matrix composition where the patches are found, especially to the eucalyptus plantation since it seems to be a better matrix than pasture areas are to the bird community.